Associação entre domínios específicos de atividade física e dor lombar crônica em idosos da comunidade - Michael Douglas da Silva Martins (2022)
OBJECTIVE: To investigate the association between specific domains of physical activity (PA) and chronic low back pain (LBP) in community-dwelling older adults. METHODS: A cross-sectional study with community-dwelling older adults (≥ 60 years), randomly recruited from a middle-size city of 207,610 people, Brazil. Data collection included sociodemographic, behavioral and health variables, PA domains measured with Modified Baecke Physical Activity Questionnaire and presence of chronic LBP. Participants in the top quartile of PA score were identified as “more active” and the remaining participants identified as “less active”. Binary logistic regression was used to test the association of domains of PA with the presence of chronic LBP. Sociodemographic, behavioral, and health variables were used as potential confounders. RESULTS: A total of 516 older adults were included. The mean age was 71.8 (95% CI: 71.1, 72.5) years and 354 (68.6%) were women. 234 (45,3%) patients reported chronic LBP, and 152 (29%), 139 (27%), 130 (25%) and 159 (31%) participants were identified as more active in the household, sports, leisure and total PA domains, respectively. After controlling for potential confounders, more active participants in sports (OR = 0.62, 95% CI: 0.40, 0.97), leisure-time (OR = 0.54, 95% CI: 0.35, 0.85) and total (OR = 0.60, 95% CI:0.39, 0.92) PA domains were less likely to report chronic LBP, when compared to less active older adults. CONCLUSION: In this study, high levels of sports, leisure-time and total PA were associated with reduced risk in reporting chronic LBP in community-dwelling older adults.